Localities of protected plants within the Folusz Protection District (Magura National Park, Southern Poland) – floristic note - Żegleń, Ewelina; Betleja, Laura (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2025)
The work presents the results of field research carried out from March to November in the Folusz Protection District within the Magura National Park. The aim of this study was to compile a list of legally protected plants occurring there and their localities. The research confirmed the occurrence of 14 protected species in the Folusz Protection District, 4 of which are under strict protection and the other 10 are partially protected. The localities of the protected plant species recorded within the Folusz Protection District are situated mainly in scrub, forest and non-forest plant communities.